Chiral supramolecular compounds comprising naphthalene-1, 5-disulfonic acid and various α-amino acids: influence of substituents of α-amino acids on the structures, circular dichroism and luminescent properties. Issue 46 (18th November 2015) - Li, Ya-Nan; Huo, Li-Hua; Zou, Xin; Deng, Zhao-Peng; Zhu, Zhi-Biao; Gao, Shan
Abstract: Self assembly of naphthalene-1, 5-disulfonic acid (1, 5-H2 NDS) and 11 chiral α-l -amino acids generates 12 chiral supramolecular compounds, namely, 2(H Ala ) + ·(NDS) 2− (1 ), 4(H Ser ) + ·2(NDS) 2− ·2(H2 O) (2 ), 2(H Phe ) + ·(NDS) 2− (3 ), 2(H Tyr ) + ·(NDS) 2− (4 ), 2(H2 Cys ) 2+ ·2(NDS) 2− ·2(H2 O) (5 ), 2(H Val ) + ·(NDS) 2− ·2( Val )·4(H2 O) (6 ), 2(H Thr ) + ·(NDS) 2− (7 ), 2(H Leu ) + ·(NDS) 2− ·2(H2 O) (8 ), 2(H Lle ) + ·(NDS) 2− ·(H2 O) (9 ), 2(H Arg ) + ·(NDS) 2− ·3(H2 O) (10 ), (H2 His ) 2+ ·(NDS) 2− ·2(H2 O) (11 ), and 2(H2 His ) 2+ ·2(NDS) 2− ·6(H2 O) (12 ), which have been characterized by elemental analysis, IR, TG, PL, circular dichroism (CD), powder and single-crystal X-ray diffraction. Structural analyses indicate that substituents of α-amino acids influence the supramolecular patterns formed by –SO3 and –NH3 groups and supramolecular networks. Compounds1–12 crystallize in different chiral P 1, P 21 21 21, P 32 and P 21 space groups, respectively. The patterns formed by –SO3 and –NH3 groups are more abundant, such as 1D double chain in1, 3 and4, [(SO3 )4 (NH3 )4 ] cage in2, [(SO3 )4 (NH3 )4 ] motif in5, [(SO3 )2 (NH3 )4 ] motif in6, 1D cylinder in7, [(SO3 )(NH3 )] motif in8, 11 and12, 1D single and double chain in9, as well as [(SO3 )2 (NH3 )2 ] motif in10 . Compounds1–9 exhibit different pillared layered networks, in which weak π⋯π and C–H⋯π interactions are detected except for compounds4, 6, 8 and9 . Compound11 presents an interesting network constructed from the interconnection of two types of DNA shaped double helixes. It should be indicated that exposure of12 under atmosphere can transform into compound11, in which the configuration of H2 His 2+ cations varies from R to S . CD spectra indicate that the solid samples of compounds3, 4 and6–11 display dichroic signals in their CD spectra. Luminescent investigation reveals that compounds1–11 exhibit stronger emission than the 1, 5-H2 NDS with the emission maximum varying from 342 to 413 nm. Graphical abstract: